Relative value of Vitamin A and carotenoids of alfalfa meal and of corn in supplying Vitamin A requirements of swine for reproduction. - Parrish, D.B.; Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
Swine commonly, obtain vitamin A from feed in the form of the provitamins- carotene and cryptoxanthin-of alfalfa and yellow corn. Swine are able to convert these provitamins to vitamin A, probably in their intestinal walls. Some commercial swine feeds contain true vitamin A, especially feeds recommended for young pigs. Nearly all the information available on the relative effectiveness of the forms of provitamin A in natural feedstuffs to supply vitamin A requirements of swine was obtained on young growing pigs. The requirements for and metabolism of, vitamin A may differ in growing pigs and sows. A study of this problem, therefore, was undertaken. Duroc gilts were placed in dry lot late in the fall. Feeding of experimental rations was begun one month before the gilts were bred. The experimental diets were composed of white corn, soybean oil meal, brewer's yeast, skimmllk powder, iodized salt, bone meal, limestone, and vitamins. The amount of various vitamin A supplements that each gilt received daily is shown for the various experiments in Tables 26, 27, and 28.
Keywords: Swine; Vitamin A; Carotenoids; Alfalfa meal; Reproduction